Acute Flaccid Myelitis: Characteristics and Outcomes of 2014 and 2016 Cases at a Single Center - Matesanz, Susan (J Pediatr, 2019)
Acute flaccid myelitis (AFM) is a rare condition associated with spinal cord gray matter abnormalities and frequent persistent motor deficits in the limbs. We present our experience with the diagnosis, management, and outcomes of affected children in 2014 and 2016, emphasizing features that should trigger early consideration of AFM. Early viral testing may increase the rate of detecting associated viruses.